Prospection of the quality and bioactive potential of the seedless watermelon - Oliveira, Milena Maria Tomaz de; Alves, Ricardo Elesbão; Silva, Leirson Rodrigues da; Barreto, Norma Danielle (Scientia Plena, 2020)
The present investigation aimed to evaluate the prospection of the quality and the bioactive potential of four seedless watermelon hybrids. Fruits were collected from the commercial farms located at the Jaguaribe-Açu agricultural Valley/RN and Jaguaribe Valley/CE, Brazil. Plant material included the hybrids ’Ashira’, ’Extasy’, ’Mickylee’ and ’Valentino’. The following parameters were evaluated: fruit weight; longitudinal and transverse diameter; fruit shape index; pulp firmness; pulp color; shell thickness; soluble solids, titratable acidity, pH, soluble solids and titratable acidity ratio, total and reducers soluble sugars, vitamin C, total carotenoids, lycopene, yellow flavonoids, total anthocyanins and total polyphenols. The trial was carried out by a completely randomized design. The comparison of means was performed using one way ANOVA at the Tukey HSD test. All the hybrids showed fruits small, i.e., “icebox” type, with mean values lower than 5.5 kg, spherical shape and a higher portion of edible pulp. The fruits showed high pulp firmness leading a great resistance to mechanical injuries sustained due to transport, besides long postharvest shelf life. ’Ashira’ showed the highest proportion of sugars present in the fruit due to the increase of 73% in the SS/AT ratio compared to the other hybrids. ’Extasy’ presented high content of total carotenoids whereas ’Ashira’ stood out in the content of total polyphenols. The hybrids are promising alternatives to the local and export watermelon market, in view of the high quality and bioactive potential linked to the good adaptability and stability under the growth conditions.